Efficacy and Safety of Infliximab Retreatment in Crohn's Disease: A Multicentre, Prospective, Observational Cohort (REGAIN) Study from the GETAID. (2nd September 2022) - Boschetti, Gilles; Nachury, Maria; Laharie, David; Roblin, Xavier; Gilletta, Cyrielle; Aubourg, Alexandre; Bourreille, Arnaud; Zallot, Camille; Hebuterne, Xavier; Buisson, Anthony; Grimaud, Jean-Charles; Bouhnik, Yoram; et al.
Abstract : INTRODUCTION: The objective of this study was to describe the efficacy and safety of infliximab (IFX) reintroduction in Crohn's disease (CD) after stopping for loss of response or intolerance. METHODS: We conducted a prospective multicenter observational cohort study including adult patients with clinically (CD Activity Index >150) and objectively active luminal CD in whom IFX was reintroduced after at least 6 months of discontinuation. The reasons for the initial discontinuation could be a secondary loss of response or IFX intolerance. The reintroduction schedule included 3 IFX infusions at weeks 0, 4, and 8, after a systematic premedication. The primary end point was the efficacy of IFX retreatment at week 26 defined by a CD Activity Index of <150 in the absence of IFX discontinuation or use of corticosteroids, surgery, or other biologic. RESULTS: At week 26, 24 patients (35%) among the 69 analyzed reached the primary end point. No significant difference was observed between rates of clinical remission at week 26 in patients with prior LOR (n = 48) and those with IFX intolerance (n = 21) (35% and 33%, P = 0.87, respectively). Thirty-two acute infusion reactions were recorded in 27 patients, leading to withdrawal of IFX in 20 patients. No pharmacokinetic characteristic at baseline but detection of positive anti-drug antibodies at week 4 was predictive of IFX failure or infusion reaction at week 26. DISCUSSION: In this first prospective cohort study, IFX retreatment was safe and effective in one-third of the patients with CD, regardless the reason of prior discontinuation. Early detection of anti-drug antibodies can predict subsequent IFX reintroduction failure and infusion reactions.